Implementation of Transformative Supervision in Improving the Quality of Project-Based Learning - Hariyadi, Ahmad; Utaminingsih, Sri; Setiadi, Gunawan; Khamdun; Shofwani, Siti Aniqoh (Universitas Negeri Semarang, 2025)
This study aims to describe the implementation of transformative supervision in improving the quality of project-based learning (PjBL) at SMAN 1 Rembang. The background of this study is based on the importance of the role of principals and supervisors in directing teachers to become reflective, creative, and innovative learning facilitators in the Merdeka Belajar era. Transformative supervision is seen as an approach that encourages cultural and structural changes in learning practices through reflective dialogue, inspirational leadership, and strengthening the professional capacity of teachers. This research method uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects included principals, subject teachers, and supervisors. The results of the study showed that the implementation of transformative supervision contributed significantly to improving the quality of planning, implementation, and evaluation of project-based learning. Participatory and empathetic supervision can encourage teachers to innovate, collaborate, and reflect on themselves continuously. The implications of this study indicate that the transformative supervision model can be an effective strategy to improve teacher professionalism and the quality of learning, especially in implementing the PjBL approach. Recommendations are given for schools to strengthen a dialogic supervision culture, support the development of teacher learning communities, and make supervision an integral part of the transformation of educational quality.